2005
DOI: 10.1128/jcm.43.9.4460-4465.2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Human Group C Rotaviruses in Bangladesh

Abstract: Group C rotaviruses were detected by reverse transcription-PCR in 14 (2.3%) of 611 group A rotavirusnegative stool specimens from the patients admitted to the International Centre for Diarrhoeal Disease Research, Bangladesh hospital, Dhaka, Bangladesh, during July to December 2003. The low rate of detection suggested that infection with group C rotaviruses was an uncommon cause of hospitalization due to gastroenteritis. In addition, coinfections with pathogenic enteric bacteria were frequently observed in grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
74
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 38 publications
4
74
1
2
Order By: Relevance
“…However, molecular analysis of human GCRV strains would not seem to support this theory, as all of the human GCRVs form a closely related group, suggesting a strong host-species restriction (2,34). These inconsistencies may be a result of the limited amount of sequence data available for animal strains.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…However, molecular analysis of human GCRV strains would not seem to support this theory, as all of the human GCRVs form a closely related group, suggesting a strong host-species restriction (2,34). These inconsistencies may be a result of the limited amount of sequence data available for animal strains.…”
mentioning
confidence: 81%
“…Human infection by GCRV has been associated with both sporadic episodes and large outbreaks of gastroenteritis in all age groups and appears to be globally distributed (1,2,5,6,18,24,25,34,38,41,43). Large-scale epidemiological studies have revealed that the prevalence may range from 0.6% to 6.8% (2,24), and GCRVs are regarded as emerging human pathogens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies on RVC from all over the world by several researchers prove that this group is as important as RVA and causes severe acute gastroenteritis in human and swine (Rahman et al 2005;Meleg et al 2008;Moon et al 2011;Marthaler et al 2013;Suzuki et al 2014). In a routine electrophoretic screening survey for RVA in swine population, we found an atypical migration pattern of genomic RNA segments from a piglet fecal specimen (Figure 1), resembling established electrophoretic pattern (4-3-2-2) of RVC (Desselberger 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Group C rotaviruses were first detected from an Australian infant hospitalized with diarrhea in 1973 (33). Since then, group C rotaviruses have been recognized as a cause of gastroenteritis in all age groups, accounting for either sporadic cases or large outbreaks of gastroenteritis in closed and semiclosed communities (8,15,20,22,31,32,(34)(35)(36)38). Cohort and seroepidemiological studies have indicated that virtually all children are infected with group A rotaviruses by 5 years of age (28,39), while the rate of infection with group C rotaviruses is much lower, and antibody prevalence usually peaks at an age of 40 to 50 years or later (14,21,37).…”
mentioning
confidence: 99%